Street wise: a programme for educating young people about citizenship, rights, responsibilities and the law - Frankel, Sam (JKP resource materials, 2009)
Street wise : a course -- Introduction -- Summary of sessions -- Getting a course started -- Adaptability -- Session 1: Young people and society -- Session overview -- Introduction to session 1 -- Society and you -- Stereotypes -- Young people as a threat -- Breaking down barriers -- What is respect -- Showing respect -- Session 2: Right and wrong -- Session overview -- Introduction to session 2 -- Is right and wrong fixed or flexible? -- The ingredients : what makes something right or wrong? -- Feelings -- Recognising other people's feelings -- Session 3 it's a crime -- Session overview -- Introduction to session 3 -- Putting forward your point -- The point of the criminal law -- Spot the crime -- Impact of crime on the offender -- Enforcing the law -- Session 4: Street law -- Session overview -- Introduction to session 4 -- Antisocial behaviour -- Stop and search 1 -- Stop and search 2 -- Arrest -- Arriving at a police station -- Session 5: Citizenship in practice -- Session overview -- Introduction to session 5 -- Course re-cap -- A crime is committed -- Search and find -- Arriving at the police station -- Advising your client -- Police interview -- Course conclusion